Communication audit of BAWASLU participatory monitoring socialisation program in South Buton - Antang, Nur; Maulana, Harry Fajar; Nurfida, Wa (Universitas Bunda Mulia, 2023)
Bawaslu's Participatory Supervision Programme is an election supervision carried out by the Election Supervisor, with a Communication Audit this programme can be seen in terms of scientific analysis to plan interventions and design communication improvement initiatives. This study aims to conduct a communication audit on the socialisation program of participatory election supervision at Bawaslu South Buton. This research method uses an Evaluative with Qualitative approach. The results of the Audit Research on the Participatory Supervision Socialisation Program in South Buton showed good results at the input stage, with internal discussions and public debates encouraging the handling of violations. However, there were still shortcomings in the substance of the programme, which led to less-than-optimal teamwork. The output stage showed adequate and targeted messages, with coordination through various activity programmes. The outcome stage showed an interest in information on electoral violations, but useful findings were relatively low due to the results-oriented and outcome-focused design of the programme. Audit results can provide valuable information to improve programme efficiency, credibility, and economy. Audit results can be used as a credible means of information for BAWASLU South Buton to improve the programme and enhance organisational performance.